RISK MANAGEMENT ANALYSIS OF E-KOHORTKIA APPLICATION USING ISO 31000 FRAMEWORK IN SOUTH CENTRAL TIMOR DISTRICT HEALTH OFFICE - Roy Armus Allu; Kristoko Dwi Hartomo (JUTI: Jurnal Ilmiah Teknologi Informasi, 2024)
The E-KohortKIA application is a web-based application launched by the Indonesian Ministry of Health for use in Puskesmas and Health Offices throughout Indonesia as a solution to various problems caused by manual use of the KIA Cohort. This application can be accessed via computer or smartphone and is currently being implemented by the South Central Timor District Health Service for Maternal and Child Health (KIA) services. In using this application, various possible risks can occur that can disrupt application performance, therefore it is necessary to carry out a risk management analysis. The aim of this research is to determine various possible risks that could occur in implementing the E-KohortKIA application and to carry out risk treatment for these possible risks. This research uses qualitative methods by collecting data through interviews and observations, as well as data processing and risk management analysis using the ISO 31000 framework including the risk assessment stage and risk treatment stage. The results of this research found 23 possible risks, most of which were due to system and infrastructure factors. These possible risks include 13 possible low level risks, 8 possible medium level risks, and 2 possible high level risks. There are 2 possible risks that have a high and maximum level of risk severity so that they have the potential to disrupt or inhibit or even stop application performance. This research also provides recommendations for risk treatment proposals for various possible risks and can be used by users to maintain application performance.